Nuclear transporter Importin-13 plays a key role in the oxidative stress transcriptional response - K. A. Gajewska (Nature Portfolio, 2021)
Importin superfamily member IPO13 mediates nuclear transport bidirectionally. Here the authors delineate the transcriptome of wild-type and IPO13-knockout mouse embryonic stem cells, revealing IPO13’s key role in the oxidative stress response through targeted transport of specific transcription factors.